The Updating of Professional Ethics: Statements, Interpretations and Recommendations of the Chilean Bar Association - Fuenzalida, Pablo (2009)
The objective of this article is to show the normative activity of the Bar Association regarding the ethics of lawyers regarding the ethics of lawyers since 1981. Likewise, the article deals with these efforts to update the good practices of the profession, to identify those statements, recommendations and interpretations that have been issued during the period 1981-2005, in view of the discussion generated within the General Council, the main organ of the College, in order to know the reasons and sources that motivated them. The first section deals with the different agreements dictated by the General Council of the College. The second section takes stock, on the one hand evaluating the updating of the rules that regulate the legal profession, and on the other criticizing the normative technique used and the content of some of the proposals. It concludes by exhorting the creation of a new code or at least a substantial reform of the CEP. In this way, it would be achieved, in a systematic way, non-fragmentary and sporadic, present norms that respond to the changes suffered in this period by the profession and, ideally, complete this work by offering some professional model to which the Bar Association aspires. This work is part of the current revision of the CEP under the current General Council, work entrusted to its Commission of Ethics and Codes of Good Professional Practice, in order to provide some relevant background, regardless of the final result of the work of this. In conclusion, although criticisms have been made, the attempt to update ethical standards before a profession that has taken on competitive, specialized and stratified characteristics must be assessed.